MODERN THERAPEUTIC APPROACHES IN FOOD ALLERGY - Monica Alexoae; Stela Gotia; Ileana Ioniuc (Amaltea Medical Publishing House, 2013)
Food allergy has a growing prevalence in children (6-8%) and represents a worrying public health problem. Despite the numerous controversies regarding the feeding in high atopic risk infants and children with food allergy, there are safe and effective drug therapies, some of them already in clinical trial phase (immunotherapy, anti-IgE agents, recombinant vaccines, Toll-like receptors agonists, chemokine and chemokine receptor antagonists).